IMPROVING THE PSYCHOLOGICAL KNOWLEDGE OF YOUNG PEOPLE ON THE VERGE OF STARTING A FAMILY - Khursanov Omadbek Ulug’bek og’lu (Bright Mind Publishing, 2025)
The article provides detailed information on the family and the relationships in it, as well as the views of psychologists on family relationships.
Keywords: Family, population, divorce, marriage, school, girl, boy, problem, difficulty, life, relationship, agreement, conflict, dispute, main factor.